A Phosphotyrosine‐Imprinted Polymer Receptor for the Recognition of Tyrosine Phosphorylated Peptides - Emgenbroich, Marco; Borrelli, Cristiana; Shinde, Sudhirkumar; Lazraq, Issam; Vilela, Filipe; Hall, Andrew J.; Oxelbark, Joakim; De Lorenzi, Ersilia; Courtois, Julien; Simanova, Anna; Verhage, Jeroen; Irgum, Knut; et al. (Chemistry : a European journal, 2008)
Hyperphosphorylation at tyrosine is commonly observed in tumor proteomes and, hence, specific phosphoproteins or phosphopeptides could serve as markers useful for cancer diagnostics and therapeutics. The analysis of such targets is, however, a challenging task, because of their commonly low abundance and the lack of robust and effective preconcentration techniques. As a robust alternative to the commonly used immunoaffinity techniques that rely on phosphotyrosine(pTyr)‐specific antibodies, we have developed an epitope‐imprinting strategy that leads to a synthetic pTyr‐selective imprinted polymer receptor. The binding site incorporates two monourea ligands placed by preorganization around a pTyr dianion template. The tight binding site displayed good binding affinities for the pTyr template, in the range of that observed for corresponding antibodies, and a clear preference for pTyr over phosphoserine (pSer). In further analogy to the antibodies, the imprinted polymer was capable of capturing short tyrosine phosphorylated peptides in the presence of an excess of their non‐phosphorylated counterparts or peptides phosphorylated at serine. A useful marker: An epitope‐imprinting strategy leads to a synthetic phosphotyrosine‐selective imprinted polymer receptor. Urea‐mediated imprinting of N,O‐protected phosphotyrosine (see picture) leads to a synthetic receptor capable of selectively extracting phosphotyrosine peptides in the presence of phosphoserine, phosphothreonine, and non‐phosphorylated peptides.